MECHANISMS FOR INCREASING EMPLOYMENT THROUGH THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP - Saitov , Sirojiddin; Asrayev , Shavkat (Scientific practical conference, 2025)
This study examines mechanisms for increasing employment in Uzbekistan through the development of social entrepreneurship. By analyzing government initiatives, donor-supported programs, and youth and women-focused entrepreneurship projects, the paper highlights how social enterprises contribute to job creation, skills development, and inclusive economic growth. Empirical evidence indicates that targeted interventions—such as USAID programs for rural women, UNDP assessments of female entrepreneurship, state trust funds for youth, and industrial-entrepreneurial zones—have expanded employment opportunities, particularly among underserved groups. The findings suggest that fostering social entrepreneurship can serve as an effective strategy for enhancing labor market participation and addressing structural employment challenges in Uzbekistan.